Risk factors of induced abortion among preparatory school student in Guraghe zone, Southern region, Ethiopia: a cross-sectional study - Kifle Lentiro; Teklemichael Gebru; Abdusemed Worku; Agizie Asfaw; Tigist Gebremariam; Addisu Tesfaye (BMC, 2019)
Abstract Background Induced abortion is a common undergo in many societies of the world. Every year, around 20 million unsafe abortions are done worldwide. From fragmented studies conducted in Ethiopia, the prevalence of induced abortion and its adverse effects are increasing over time. The aim of this study was to assess factors associated with induced abortion among female preparatory school students in Guraghe zone. Methods A cross-sectional study was conducted among female students of preparatory schools in April 2017. Systematic random sampling technique was employed to select 404 students from the total of 3960 female preparatory school students in the study area. Data was collected through self-administered questionnaires. Descriptive summary, binary and multivariate analyses were underwent to identify factors associated with induced abortion. The study was ethically approved by institutional review board of Wolkite University. Results The response rate of this study was 98.3%. The lifetime prevalence of induced abortion among young preparatory schools students whose age range from 15 to 22 years was 13.6% [95% CI (10.4, 17.1)]. The odds of induced abortion undergo was 2.3 times more likely in rural family residents [AOR = 2.3, 95% CI (1.1, 4.8)] as compared to that of urban family residents. Students without sexual health education were 6.4 times more likely to undergo induced abortion as compared to those who got sexual health education at sc0000hool [AOR = 6.4, 95% CI (3.1, 13.1)]. Furthermore, students who drank alcohol often were 4 times [AOR = 4.0, 95% CI (1.1, 14.2)] more likely to undergo induced abortion and students who consumed alcohol sometimes had 3.3 times [AOR: 3.3, 95%CI (1.4, 8.1)] the risk of induced abortion compared with girls with no history of alcohol consumption. Conclusion A high lifetime prevalence of induced abortion among young adolescent was observed. Being rural residence, not having reproductive health education, and alcohol consumption were found to be independent predictors of induced abortion undergo. Therefore, IEC/BCC programs with special emphasis on youth friendly sexual and reproductive health services should be strengthened to reduce induced abortion.